2020
DOI: 10.1177/0300891620901745
|View full text |Cite
|
Sign up to set email alerts
|

Additional value of MRI-detected EMVI scoring system in rectal cancer: applicability in predicting synchronous metastasis

Abstract: Introduction: Extramural vascular invasion (EMVI) has been recommended as an independent prognostic factor for poor overall survival rate in rectal cancer and can be used as a potential biomarker. Early prediction of prevalence of synchronous metastasis can elevate the disease-free survival rate. We aimed to evaluate the magnetic resonance imaging (MRI)–detected EMVI (mrEMVI) scoring system in predicting distant metastasis in T3 rectal cancer. Methods: Patients with postoperative histopathologically confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Sohn et al 20 found that mrEMVI was a risk factor for distant metastasis of rectal cancer, and patients with mrEMVI-positive before treatment had a significantly higher risk of distant metastasis. Tripathi et al 21 found that mrEMVI-positive was an independent risk factor for synchronous distant metastasis of rectal cancer. In a recent meta-analysis, mrEMVI-positive patients had a five-fold increased incidence of synchronous metastases and an approximately 4-fold increased risk of postoperative metachronous metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sohn et al 20 found that mrEMVI was a risk factor for distant metastasis of rectal cancer, and patients with mrEMVI-positive before treatment had a significantly higher risk of distant metastasis. Tripathi et al 21 found that mrEMVI-positive was an independent risk factor for synchronous distant metastasis of rectal cancer. In a recent meta-analysis, mrEMVI-positive patients had a five-fold increased incidence of synchronous metastases and an approximately 4-fold increased risk of postoperative metachronous metastases.…”
Section: Discussionmentioning
confidence: 99%
“… 28 - 30 Studies had shown that lymph node metastasis was associated with distant metastasis after colorectal cancer surgery, 28 , 29 and N stage was associated with the presence of synchronous distant metastasis in rectal cancer. 21 , 30 The assessment of lymph node metastasis mainly includes 2 aspects, the number and the location of lymph node metastases. It had been established that lymph node metastasis was an important independent prognostic factor for rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For rectal cancer patients with EMVI status, the original low-signal vascular shadow on MRI is replaced by a moderate tumor signal (i.e., a continuous extension of the tumor signal in the vascular structure outside the intestinal wall), and the tumor signal leads to continuous or discontinuous vascular expansion ( 7 ). The Mercury research group has proposed a 5-point MRI scoring system to evaluate EMVI in rectal cancer: 0: the mass penetrates the rectum wall but is smooth externally with no adjacent vessels, and MRI evaluation; 1: the mass extends in strips through the rectum wall, no adjacent vessels; 2: the mass extends in strips through the rectum wall, adjacent blood vessels, but no tumor-like signal was found in the vascular lumen, MRI evaluation; 3: the mass extends in strips through the rectum wall, adjacent blood vessels showed moderate tumor-like signal in the lumen, lumen widening, and MRI evaluation; 4: a moderate tumor-like signal in the lumen of the adjacent large vessels (above/middle/lower rectal veins) with an irregular vascular outline, MRI evaluation ( 8 ). A 5-grade scoring system using MRI to predict EMVI was created.…”
Section: Introductionmentioning
confidence: 99%
“…2,[6][7][8] Magnetic resonance imaging-detected extramural vascular invasion (mrEMVI), which can independently predict local and distant metastasis, is an important prognostic factor. [9][10][11][12][13][14][15][16][17][18] It has been shown to correlate with relapse-free survival and overall survival. 9,12,13,19 The majority of recent studies concerning mrEMVI status focused only on disease-free survival (DFS), overall survival (OS), posttreatment effects, and magnetic resonance imaging (MRI) diagnosis accuracy.…”
Section: Introductionmentioning
confidence: 99%